ショウワ キチ シュウヘン ノ エンコ ノ スイシツ ノ ユライ ト ヘンカ - 平林, 順一; ヒラバヤシ, ジュンイチ; 小坂, 丈予; オサカ, ジョウヨ; HIRABAYASHI, Jun-ichi; OSSAKA, Joyo (国立極地研究所, 1977)
P(論文) :1972年12月から1974年2月の間に,南極昭和基地周辺の露岩地域で行った湖沼調査の結果に基づき,ラングホブデ,スカルブスネス,西オングル島の総塩分量が,10 g/l以上の塩湖の水質について検討を試みた.またこの地域の塩湖とビクトリアランド,ドライバレー地域の主な塩湖の水質を,THOMPSONらが行った海水の冷凍濃縮実験の結果に基づいて比較し,その水質の由来を考察した.昭和基地周辺の塩湖は海水組成に近く,また冷凍濃縮過程としては,初期段階のものがほとんどであると考えられる.これにくらベドライバレー地域においては,種々の段階の塩湖が存在している.またラングホブデ,スカルブスネスに存在する主な塩湖について,表面水ならびに各層水の水質の季節変化についても調査を行った.その結果,ほとんどの塩湖の表面水の成分濃度は,夏期には周辺からの融雪水などにより希薄であり,冬期には充分な混合が行われるために濃くなっている. For a period from December 1972 to February 1974, we made researches on the lakes around Syowa Station. The present paper deals with the consideration about chemical compositions of the lakes in Langhovde, Skarvsnes and West Ongul Island, in which the total concentration of salts is more than 10 g/l. Furthermore, from the comparison with the chemical compositions of main lake waters in the Dry Valley area, on the basis of the experimental results by T. G. THOMPSON and K. H. NELSON about the "enrichment process of sea water under frigid condition", we discussed the origin of the chemical components of these lake waters as follows: Chemical compositions of saline lake waters around Syowa Station are similar to those of sea water. Most of these lakes are in the early stage of the "enrichment process of sea water under frigid condition"; whereas saline lakes in the Dry Valley area are in various stages. According to the chemical analysis of surface and layered water of saline lakes in Langhovde and Skarvsnes, seasonal variations are observed that the concentrations of chemical compositions of surface waters decreased in summer due to the inflow of the thawing water and increased in winter due to the sufficient circulation in the lake. departmental bulletin paper